Four new species of Oedalea (Diptera, Empidoidea, Hybotidae, Oedaleinae) from China with a key to south eastern Asian species - Zeng, Wei; Lin, Chen; Yang, Ding (Zootaxa, 2022)
Previously only two species of the genus Oedalea were known from China. Here the following four new species are added to the fauna of China from Yunnan Province, Hebei Province and Tibet Autonomous Region: O. linzhiensis sp. nov., O. wenliangi sp. nov., O. wulingshana sp. nov. and O. yangi sp. nov. A key to the species of Oedalea from south eastern Asia is provided.